Assisted dying: reflections on the psychological process. Issue 1 (13th April 2022) - Kelly, Tom
Abstract: This paper explores the question of assisted dying from both a legal and psychological perspective within the legal parameters in place at the time of writing of this paper. Links are made between Kohut's notion of an acceptance of the finiteness of existence and of transience as one of several indicators of the maturation and transformation of archaic narcissism, and Jung's notion of the readiness and ability to ' die with life' as the goal of the second half of life. The author raises awareness of the importance of the need for clarity with regard to these issues on the part of therapists who may be required to provide an evaluation of a patient's admissibility to a service of assisted dying. Abstract : Cet article explore le sujet de l'aide à la mort, à la fois du point de vue légal et psychologique, dans les paramètres légaux en place au moment de son écriture. L'article fait des liens entre la notion de Kohut ‐ l'acceptation de l'aspect fini de l'existence et de son caractère éphémère comme l'un des indicateurs de la maturation et de la transformation du narcissisme archaïque ‐ et l'idée de Jung selon laquelle le but de la seconde moitié de la vie est de développer sa capacité à « mourir avec la vie ». L'auteur attire l'attention sur l'importance du besoin de clarté concernant ces questions chez les thérapeutes auxquels on pourrait demander de fournir une évaluation de l'admissibilité d'un patient dans un service d'aide à la mort. Abstract : Dieser Beitrag untersucht die Frage der Sterbehilfe sowohl aus rechtlicher als auch aus psychologischer Sicht innerhalb der zum Zeitpunkt der Abfassung dieses Beitrags bestehenden rechtlichen Rahmenbedingungen. Es werden Verbindungen hergestellt zwischen Kohuts Vorstellung von der Akzeptanz der Endlichkeit des Daseins und der Vergänglichkeit als einem von mehreren Indikatoren für die Reifung und Transformation des archaischen Narzißmus und Jungs Vorstellung von der Bereitschaft und Fähigkeit, 'mit dem Leben zu sterben' als Ziel der zweite Lebenshälfte. Der Autor sensibilisiert für die Notwendigkeit der Klärung dieser Fragen seitens der Therapeuten, die möglicherweise eine Beurteilung der Zulässigkeit eines Patienten zu einer Sterbehilfe abgeben müssen. Abstract : Questo articolo esplora la questione della morte assistita sia da una prospettiva legale che psicologica all'interno dei parametri legali in vigore al momento della stesura di questo articolo. Vengono creati collegamenti tra la nozione di Kohut di accettazione della finitezza dell'esistenza e della transitorietà come uno dei numerosi indicatori della maturazione e trasformazione del narcisismo arcaico, e la nozione di Jung della disponibilità e capacità di 'morire con la vita' come obiettivo della seconda metà della vita. L'Autore sensibilizza sulla necessità di chiarezza rispetto a queste problematiche da parte dei terapeuti che possono essere chiamati a fornire una valutazione sull'ammissibilità di un paziente ad un servizio di morte assistita. Abstract : В данной статье рассматривается вопрос об эвтаназии как с правовой, так и с психологической точки зрения в рамках правовых параметров, действующих на момент написания этой статьи. Проводятся параллели между представлением Кохута о принятии конечности существования и быстротечности как одного из нескольких индикаторов созревания и трансформации архаического нарциссизма и представлением Юнга о готовности и способности «умереть вместе с жизнью» как цели второй половины жизни. Автор обращает внимание на необходимость ясности в отношении этих вопросов у терапевтов, от которых может потребоваться оценка допустимости эвтаназии у конкретного пациента. Abstract : El presente trabajo explora el tema del acompañar el proceso de morir desde una perspectiva legal y psicológica en el marco de los parámetros legales existentes al momento de escribir el trabajo. Se plantean conexiones entre la noción de Kohut, de aceptación de la finitud de la existencia y la de transitoriedad como uno de los muchos indicadores de maduración y transformación del narcisismo primitivo, y la noción de Jung de disponibilidad y habilidad para 'morir con vida' como meta en la segunda mitad de la vida. El autor trae a la consciencia la importancia de la necesidad de claridad con respecto a estas cuestiones por parte de terapeutas quienes pueden ser requeridos para dar una evaluación sobre la admisibilidad de un paciente a un servicio de muerte asistida. Abstract : 安乐死:在心理历程上的反思 作者在安乐死合法化的时期写下这篇文章, 来探索关于安乐死的法律和心理层面。文章把一些观念进行了联系, 它们是科胡特接纳有限的存在的观点、把接纳无常作为一种成熟和从原始自恋中转化的指征、以及荣格的准备好和有能力"向死而生"作为后半生目标的观念。作者提示人们需要重视这一点, 即当治疗师被要求评估病人接受安乐死服务的适用性时, 我们需要从这些层面的议题去进行辨析。 Abstract : Este artigo explora a questão da morte assistida de uma perspectiva jurídica e psicológica dentro dos parâmetros legais em vigor no momento da redação deste artigo. São feitas ligações entre a noção de Kohut de aceitação da finitude da existência e da transitoriedade como um dos vários indicadores da maturação e transformação do narcisismo arcaico, e a noção de Jung da prontidão e capacidade de "morrer com vida" como o objetivo da segunda metade da vida. O autor conscientiza sobre a importância da necessidade de clareza em relação a essas questões por parte dos terapeutas que podem ser obrigados a fornecer uma avaliação da admissibilidade de um paciente a um serviço de morte assistida.